Pacing strategies for distance events in 2012 U.S. Olympic Track and Field Trials - Hirt, M.; Henson, P. (Techniques Magazine, 2012)
The purpose of this article is to examine pacing techniques in both the men`s and women`s distance races (from the 800 meters to the 10,000 meters) in the 2012 U.S. Olympic Track and Field Trials. These races are different from many other championship races because qualification standards have to be met in order to make the Olympic team. Therefore, the question of interest is: are the pacing strategies at the Olympic trials different? Often times, for distance races (above 800 meters) at championship events, the winners negative split the race, running the second half faster than the first. Is that the case in the 2012 U.S. Track and Field Olympic trials?